Politicization of Hadith in the Media: Analysis of the Use of Religion as an Instrument for Political Campaigns - Fauzan Akbar; Asrar Mabrur Faza; Rahmi Syahriza (Penerbit Hellow Pustaka, 2025)
Politicization of hadith in the media has become an increasingly visible phenomenon in various political campaigns, where religion is often used as a tool to influence public opinion and strengthen the support base. The background problem in this study relates to the widespread use of hadith in the media to support or attack certain political figures, as well as its impact on people's perceptions of religion and politics. The aim of this research is to analyze how hadith is used in the media as an instrument for political campaigns, as well as its impact on people's understanding of religion. This research uses qualitative methods using content analysis techniques for media reports and political campaign materials involving hadith quotations. Results show that hadiths are often twisted or quoted selectively to support specific political narratives, with the aim of establishing political legitimacy or diverting public attention from substantive issues. The conclusion of this research is that the politicization of hadith in the media has the potential to undermine authentic religious understanding and exacerbate social polarization, and demands ethical supervision in the use of religion in the public sphere.